Impact loading sandwich beam - Leonenko, Д.В. (Chrezvychaynye situatsii: obrazovanie i nauka, 2007)
Considered fluctuations sandwich beam under the action of impact points power. For the kinematics description of carryings layers accepted the hypotheses Bernoulli. In hard compressed filler the precise ratio of a theory of elastic strength with linear approximating of movements of his its points from cross-sectional coordinate z are fair. Received the analytical deciding and conducted their numeric and comparative analysis.